Ecotoxicological potential of bordeaux mixture and Neem oil on non-Target soil organisms - Rosa V.M.D.* (2017)
© 2017 Universidade Federal Rural de Pernambuco. All rights reserved.The use of alternative pesticides has as main function to maximize agricultural production with little or no environmental impact. However, due to the lack of studies and repeated application in certain cultures it is important to check whether there are adverse effects on non-Target soil organisms. Thus, the aim of this study was to evaluate the effect of Neem oil and Bordeaux mixture on survival and reproduction Enchytraeus crypticus and Folsomia candida. The tests followed the relevant standards, where the pesticides are applied separately in tropical artificial soil, the tested doses 0, 0.3, 0.5, 1, 3 and 5%, corresponding to concentrations of 0.41, 0.69, 1.38, 4.15 and 6.91 mg g-1 soil. Effects on the organisms survival were only observed at doses equal to or higher than 3%. However, doses equal to or less than recommended (1%) had negative effects on reproduction. These results have a potential impact of Neem oil and Bordeaux mixture on non-Target soil organisms, which must be proven with field studies.